Fundamentos juslaborais : tensão contemporânea entre a proteção rígida e a flexível e seus reflexos na autonomia privada coletiva - Silva, Wellington Cavalcanti da (2021)
This research aims to present private autonomy, especially collective autonomy, as one of the reflections of the dichotomy between the rigidity and flexibilization of the labor standard, in the face of an evident standardization of worker protection before their employer, a relationship that is subject to transformations. caused by the impacts of constant technological advances and economic crises. In this bias, the dialectical method is adopted, using the syllogism as an approach for the proposed study, through bibliographic research and theoretical-normative investigation.